AMERICAN DREAM AS SEEN IN THE NOVEL “THE GREAT GATSBY” OF FRANCIS SCOTT KEY FITZGERALD = GIẤC MƠ MỸ TRONG TIỂU THUYẾT “GATSBY VĨ ĐẠI” CỦA FRANCIS SCOTT KEY FITZGERALD - Phạm, Thị Thùy Linh (2021)
This thesis concerns the analysis of the American Dream – its original features and the deterioration in Jazz Age as described in “The Great Gatsby” by Francis Scott Key Fitzgerald, including three parts with different aspects, especially the part 2 “Development”. The first part is the introduction, in which I present some main reasons, aims, working methods and the scope of the study. The second part is development which is divided in three chapters. Chapter one is devoted to some literary theories in brief and American literature at the turns of twentieth century as well as the notable features of American society in Jazz Age. Additionally, this chapter also provides the readers with necessary information on F. Scott Key Fitzgerald’s life and career in general, and his novel “the Great Gatsby” in particular. Chapter two states the original dream depicted in the novel, and discusses in some depth the three main issues exposed the decay of the American Dream in Jazz Age.